The Development and the Importance of Asian Agricultural Sector in Global Economy - Kita, Katarzyna (Rozwój i znaczenie azjatyckich rynków rolnych w gospodarce światowej, 2010)
The study is an attempt to characterize changes in production and consumption of selected agri-food products in the countries of Southeast Asia. The author analyzes a foreign agricultural trade, including especially the changes in export and import in value as well as changes in shares in international agricultural trade. The purpose of paper is to characterize the main development trends in Asian agricultural markets and their role in the global economy.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 220-228
Keywords: Southeast Asia; agricultural trade; agri-food sector; newly industrialized economies